2010
DOI: 10.1590/s1984-29612010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Association between seropositivity for Neospora caninum and reproductive performance of beef heifers in the Pantanal of Mato Grosso do Sul, Brazil

Abstract: Neospora caninum is an obligate intracellular parasite that can infect domestic and wild canids, ruminants, and horses. The purpose of this study was to evaluate the association between the presence of antibodies to N. caninum and reproductive loss in beef heifers in the South Pantanal region of Mato Grosso, Brazil. A total of 1098 heifers were evaluated from breeding to calving with regard to reproductive performance, and serology for neosporosis was assayed by indirect immunofluorescence reaction. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…None of the dogs younger than one year old had antibodies against N. caninum, and seven of the nine positive dogs were older than eight years of age, thus indicating, in the same way shown earlier regarding T. gondii, that the prevalence increased with increasing age of the animals. Other studies carried out in Brazil and in other countries have also observed higher prevalence among older animals (Andreotti et al, 2004;Oliveira et al, 2004;Capelli et al, 2004).…”
Section: Discussionmentioning
confidence: 64%
“…None of the dogs younger than one year old had antibodies against N. caninum, and seven of the nine positive dogs were older than eight years of age, thus indicating, in the same way shown earlier regarding T. gondii, that the prevalence increased with increasing age of the animals. Other studies carried out in Brazil and in other countries have also observed higher prevalence among older animals (Andreotti et al, 2004;Oliveira et al, 2004;Capelli et al, 2004).…”
Section: Discussionmentioning
confidence: 64%
“…However, an additional study should be performed to analyze the aborted fetus to confirm the infection and lesions by N. caninum. Andreotti et al (2010) demonstrated in a study conducted in beef cattle herds from Brazil's southern Pantanal wetland of the Mato Grosso Sul state, that the presence of N. caninum seropositive heifers has caused a significant impact on reproduction, with a reduction of 21.88% in the extraction rate of the herd. Furthermore, there was a negative impact on the herd benefit rate with the presence Brazil (BARROS et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted in different regions of Brazil to detect anti-N. caninum IgG antibodies in cattle, whose prevalence ranges from 9.1% to 97.2% (Hasegawa et al, 2004;Vianna et al, 2008;Andreotti et al, 2010;Amaral et al, 2012;Silva et al, 2017). In the Amazon region, N. caninum infection has been described in the states of Pará (Minervino et al, 2008;Silva et al, 2017), Rondônia (Aguiar et al, 2006;Boas et al, 2015) and Tocantins (Martins et al, 2011), with prevalence rates varying from 10.4% to 52%.…”
Section: Introductionmentioning
confidence: 99%